Use of the internet in newsgathering : a case study of The Post newspaper in Zambia - Hamachila, Alphonsius (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The Internet and World Wide Web have become dominant newsgathering tools in a sholi period of time. While the body of research, particularly in the First World, has developed quickly along with the Web, many unanswered questions remain on how journalists in developing countries make use of the Internet for newsgathering purposes. This study combined social constructivist theory with the socio-organisational and cultural approaches to news production in order to critically investigate how journalists at The Post newspaper in Zambia relate to, and make use of, the Internet as a newsgathering resource, in the context of Third World conditions. The study critiqued technological detelminism perspectives on journalists' use of the new information technology. The technological determinism theory, which has largely been advanced by some scholars from the developed world, takes a celebratory approach to journalists' use of the Internet in the newsroom. Using qualitative semi-structured interviews and observations, the study established that while journalists at The Post acknowledged the lnternet's potential in news gathering, factors such as unreliable telecommunications infrastructure, poor Internet skills, lack of local content on the World Wide Web, and organisational and occupational demands inhibited the use of the Internet as a journalistic newsgathering resource. The study established further that online reporting is only a tool within the broader news gathering and production process; and in the case of The Post, it does not replace the traditional news gathering techniques used by journalists, particularly direct contacts with human sources. The respondents cited face-to-face interviews, a traditional means of newsgathering, as the main driving force in news gathering routines at the newspaper. However, although the respondents saw some mixed blessings in the Internet as a reporting tool, they also believed that the benefits outweighed the problems.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Post -- Zambia -- Lusaka; Electronic news gathering -- Zambia -- Case studies; Journalism -- Data processing -- Zambia -- Case studies; Reporters and reporting -- Zambia -- Case studies